1991
DOI: 10.1079/bjn19910080
|View full text |Cite
|
Sign up to set email alerts
|

Activities of enzymes of the pancreas, and the lumen and mucosa of the small intestine in growing broiler cockerels fed on tannin-containing diets

Abstract: Diets containing vegetable tannins, predominantly hydrolysable gallotannins, at levels of 13.5, 25 and 50 g/kg were fed to growing broiler cockerels to examine their effect on enzymes in the pancreas, the intestinal lumen and the intestinal mucosa. Pancreas weight per unit live weight showed a significant (P < 0.05) increase with increasing level of dietary tannin while that of the liver remained unaffected. Trypsin (EC 3 . 4 . 2 1 .4) and a-amylase (EC 3.2.1.1) activities in the pancreas of birds fed at the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
57
1
4

Year Published

2000
2000
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(70 citation statements)
references
References 29 publications
7
57
1
4
Order By: Relevance
“…This might be sufficient to interact with protein of coffee pulp and should be not enough to complex those from other ingredients, considering the previous described 1:2 optimum polyphenol/protein ratio. Significant inhibition of trypsin from intestinal lumen and dipeptidase for intestinal mucosa have been observed on broiler cockerel with a tannin incorporation level of 13.5 g kg -1 food dry matter (Ahmed et al, 1991). Considering tannin level given for coffee pulp, amount of coffee pulp used in our experiment could be sufficient to induce such inhibition.…”
Section: Discussionmentioning
confidence: 79%
“…This might be sufficient to interact with protein of coffee pulp and should be not enough to complex those from other ingredients, considering the previous described 1:2 optimum polyphenol/protein ratio. Significant inhibition of trypsin from intestinal lumen and dipeptidase for intestinal mucosa have been observed on broiler cockerel with a tannin incorporation level of 13.5 g kg -1 food dry matter (Ahmed et al, 1991). Considering tannin level given for coffee pulp, amount of coffee pulp used in our experiment could be sufficient to induce such inhibition.…”
Section: Discussionmentioning
confidence: 79%
“…Also in the current study, pancreas weight was not affected by OA, which is in line with other studies (Longstuff & Mc Nab, 1991;Nyacotti et al, 1996). Conversely, in some previous studies (Ahmed et al, 1991;Mahmood et al, 2008), pancreatic hypertrophy was observed in broilers given high-tannin diets. Because pancreatic enzymes are inhibited by tannins, their production would be increased by the pancreas.…”
Section: Resultsmentioning
confidence: 92%
“…Because pancreatic enzymes are inhibited by tannins, their production would be increased by the pancreas. This condition could increase the weight of the pancreas (Ahmed et al, 1991). Birds response to dietary tannins is influenced by factors such as the source of the tannins and feedstuffs, tannin concentration, animal species, age and production level, the response parameters (weight gain, feed intake and feed efficiency), length of the test period, and diet composition (level and source of protein) (Jansman, 1993).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, such findings were obtained in monogastric animals. Ahmed et al (1991) reported that feeding growing broiler cockerels diet with increasing level of tannins, significantly increased weight of pancreas in comparison to control birds. It was probably because of higher activities of trypsin and α-amylase.…”
Section: Discussionmentioning
confidence: 99%